2021
DOI: 10.1088/1755-1315/648/1/012099
|View full text |Cite
|
Sign up to set email alerts
|

Excessive amount of rainfall decreases oil palm yield on well-drained peatland

Abstract: Low inputs of smallholder plantation in drained peatland causes the low oil palm yield. Extreme environmental factors in tropics, such as excessive rainfall, may also reduce the yield. The research objective was to evaluate the effect of the amount of rainfall on oil palm fresh fruit bunch (FFB) yield. Two study sites with different drainage condition of well (WD) and fair (FD) drained oil palm plantations on peatland was carried out from 2018 to 2019 in Jambi Province, Indonesia. The daily rainfall was monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Following a brief period of depressed stomatal conductance and photosynthesis the palms appeared to recover, likely due to an observed proliferation of fine roots at the soil surface produced in response to the water logging. This resilience to waterlogging was also seen in the field experiments of Peralta-Lobo et al (1985) and Marwanto and Hendri (2021), who reported that excessive drainage during periods of high rainfall resulted in nutrient leaching and negative impacts on FFB yield and showed that palms could be resilient, or even benefit, from periods of inundation though this resilience may only last for a short time before restrictions on root respiration begin to impair water and nutrient uptake (Woittiez et al, 2017). It is possible that substantial lateral flow of ground water, due to operation of water control gates in drainage channels, may promote aeration of the soil water and reduce anaerobic conditions, even where WTD is within the rooting zone (Henson et al, 2008).…”
Section: Introductionsupporting
confidence: 70%
“…Following a brief period of depressed stomatal conductance and photosynthesis the palms appeared to recover, likely due to an observed proliferation of fine roots at the soil surface produced in response to the water logging. This resilience to waterlogging was also seen in the field experiments of Peralta-Lobo et al (1985) and Marwanto and Hendri (2021), who reported that excessive drainage during periods of high rainfall resulted in nutrient leaching and negative impacts on FFB yield and showed that palms could be resilient, or even benefit, from periods of inundation though this resilience may only last for a short time before restrictions on root respiration begin to impair water and nutrient uptake (Woittiez et al, 2017). It is possible that substantial lateral flow of ground water, due to operation of water control gates in drainage channels, may promote aeration of the soil water and reduce anaerobic conditions, even where WTD is within the rooting zone (Henson et al, 2008).…”
Section: Introductionsupporting
confidence: 70%
“…High rainfall can also cause surface flow to carry fertilizers, resulting in low crop production [15,16]. Inundation stress activates the plant's defense mechanism, which initially affects the root organs to support plant growth and ultimately impacts oil palm production.…”
Section: Relationship Between Rainfall Rainy Days and Oil Palm Produc...mentioning
confidence: 99%